The Relevance of cross-cultural leadership training : a case study of a Finnish training program for Chinese school principals - Xing, Xin (2013)
Quality leadership training has a positive effect on school leaders. Although there is an increased interest in overseas training for educational leaders in China, little is known about the leadership practices and professional development of school leaders. This study explored Chinese school principals’ perceptions of leadership practices and professional development after undertaking a Finnish training program in October 2011. The data were collected by semi-structured interviews from six Shanghai principals and analyzed by inductive content analysis. The findings showed this training has affected Chinese principals’ work positively, including creating more effective leadership, handling the contradiction better, a wider understanding of the nature of education and the government’s role in education, and revealing reasons behind the Finnish PISA success. However, there were some lacking aspects during the training, such as limited school visits, diversified needs of trainees, irrelevant issues, incapability of some trainers, and language barriers. Hence, the principals suggested improving program quality, addressing language issues, and including Chinese authorities in the future. Nonetheless, certain issues do not work. The reasons included contextual differences in national, cultural, educational systems, principals’ tasks, teachers’ capacities, and students’ learning styles. The study assists other overseas tertiary institutions conducting cross-cultural training programs for Chinese principals. The leadership practices framework may be useful to training providers when designing and implementing leadership training programs. This study was primarily interpretative and based on the interview responses. Further research is suggested to evaluate the long-term effect of these programs, through collaboration among relevant stakeholders.